Maslow's Eupsychian Management - Afroz, Nishat (Prabandhan: Indian Journal of Management, 2012)
The paper introduces Maslow's utopian vision of managing people at work. Drawing upon the notion of self-actualization, Maslow coined the term 'Eupsychia'. It refers to an ideal culture that might be created under the most favourable circumstances. Maslow thought that such an ideal culture would facilitate self-actualization of people. He saw Eupsychian Management as a managerial philosophy that would create an environment in which people could achieve self-actualization though their work. Maslow believed that the work life of people were the main ingredient of achieving self-actualization. Maslow has done more to change our view of human nature and human possibilities than any other psychologist. His influence, both direct and indirect, continues to grow, especially in the fields of health, education, and management theory, and in the personal and social lives of the individuals. In this paper, the author has tried to elaborate on the key implication of Maslow's ideas on managing people and organizations and how these principles have been applied in the work context.